Cardiovascular Disease in Racial and Ethnic Minorities - Ferdinand, Keith C.; Armani, Annemarie; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Cardiovascular heart disease mortality in African Americans is the highest of all major racial/ethnic subpopulations in the United States. Examining race and ethnicity, Cardiovascular Disease in Racial and Ethnic Minorities will reveal that there are unacceptable healthcare disparities in risk factor prevalence, disease states, and cardiovascular outcomes in the United States. Written by a team of experts, Cardiovascular Disease in Racial and Ethnic Minorities examines to what degree biomedical and scientific literature can clarify the impact of genetic variation versus environment as related to cardiovascular disease. Chapters illustrate the magnitude of cardiovascular and metabolic disparities and the effect of environment on diseases.
Cardiovascular Disease in Racial/Ethnic Minorities: Overview and Perspectives -- Epidemiology of Cardiovascular Diseases and Risk Factors Among Racial/Ethnic Populations in the United States -- Unmasking Racial/Ethnic Disparities in Cardiovascular Disease: Nutritional, Socioeconomic, Cultural, and Health-Care-Related Contributions -- Race and Genetics -- Race, Genetics and Cardiovascular Disease -- Hypertension and Stroke in Racial/Ethnic Groups -- Dyslipidemia in Racial/Ethnic Groups -- Novel & Emerging Risk Factors in Racial/Ethnic Groups -- Weight Loss Interventions to Control Blood Pressure in an Increasingly Overweight, Multi-ethnic Society -- Obesity and the Cardiometabolic Syndrome: Impact on Chronic Kidney Disease and CVD -- Risk Calculation and Clustering Within Racial/Ethnic Groups -- Cardiovascular Imaging in Racial/Ethnic Populations: Implications for the Adequate Application of Cardiovascular Imaging Techniques Guided by Racial/Ethnic Risk Factor Variations -- Unique Aspects of Vascular and Cardiac Ultrasound in Racial/Ethnic Groups -- Heart Failure in Racial/Ethnic Groups -- Minority Women and Cardiovascular Disease.
Keywords: Medicine; Family medicine; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Internal Medicine; General Practice / Family Medicine